2019
DOI: 10.3390/biom9110751
|View full text |Cite
|
Sign up to set email alerts
|

Natural CLA-Enriched Lamb Meat Fat Modifies Tissue Fatty Acid Profile and Increases n-3 HUFA Score in Obese Zucker Rats

Abstract: Ruminant fats are characterized by different levels of conjugated linoleic acid (CLA) and α-linolenic acid (18:3n-3, ALA), according to animal diet. Tissue fatty acids and their N-acylethanolamides were analyzed in male obese Zucker rats fed diets containing lamb meat fat with different fatty acid profiles: (A) enriched in CLA; (B) enriched in ALA and low in CLA; (C) low in ALA and CLA; and one containing a mixture of olive and corn oils: (D) high in linoleic acid (18:2n-6, LA) and ALA, in order to evaluate ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The numerous and contrasting biological effects reported for CLA ( Benjamin et al, 2015 ) are probably due to its pleiotropic properties, and may not be explained by a single biochemical mechanism ( Kennedy et al, 2008 ), although they are generally ascribed to its activities on lipid and energy metabolism. CLA metabolism, extensively studied especially in rodents ( Banni et al, 1995 ; Belury and KempaSteczko, 1997 ; Sebedio et al, 1997 ), probably influences the metabolism of n-6 polyunsaturated FAs (PUFA) by competing for their formation ( Banni et al, 1999 ; Banni, 2002 ) and enhances the formation of docosahexaenoic acid (DHA, 22:6 n-3) in experimental animals ( Piras et al, 2015 ; Carta et al, 2019 ) and humans ( Murru et al, 2018 ), by inducing peroxisomal β-oxidation ( Ferdinandusse et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The numerous and contrasting biological effects reported for CLA ( Benjamin et al, 2015 ) are probably due to its pleiotropic properties, and may not be explained by a single biochemical mechanism ( Kennedy et al, 2008 ), although they are generally ascribed to its activities on lipid and energy metabolism. CLA metabolism, extensively studied especially in rodents ( Banni et al, 1995 ; Belury and KempaSteczko, 1997 ; Sebedio et al, 1997 ), probably influences the metabolism of n-6 polyunsaturated FAs (PUFA) by competing for their formation ( Banni et al, 1999 ; Banni, 2002 ) and enhances the formation of docosahexaenoic acid (DHA, 22:6 n-3) in experimental animals ( Piras et al, 2015 ; Carta et al, 2019 ) and humans ( Murru et al, 2018 ), by inducing peroxisomal β-oxidation ( Ferdinandusse et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…CLA and its desaturated and elongated metabolites are likely biosynthesized and then transported to extrahepatic tissues, as evidenced by their high concentration also in plasma and adipose tissue after dietary CLA administration. Given that modification of FA profile in the brain by dietary FAs is quite difficult ( Zamberletti et al, 2017 ; Carta et al, 2019 ; Carta et al, 2020 ), this is also true for dietary CLA.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, pharmacological activation of PPARα should be co-adjuvated with dietary supplementation of n3-PUFA. On the other hand, by feeding obese rats with CLA, a natural PPARα ligand, we detected an increase in 22:6n3 biosynthesis and thus of the n3-HUFA score in liver [33,34]. Furthermore, in mildly hypercholesterolemic subjects [35] and healthy adults [16], we found that dietary CLA-and 18:3n3-enriched cheese improved the n3-HUFA score in plasma [16].…”
Section: Discussionmentioning
confidence: 74%